Synergistic Effects of OWAS and KIM Assessment Methods in a Comprehensive Ergonomic Analysis - Krhač Andrašec, Eva; Urh, Benjamin (Vloga naprednih tehnologij v inženiringu poslovnih sistemov, 2025)
The study was conducted at the Laboratory of Enterprise Engineering (LIPPS), where we analysed the body postures of workers on a simulated assembly line. The OWAS (OVAKO Working Postures Analysis System) and KIM (Key Indicator Method) were used to identify critical body postures in the work process. The main aim of the research was to explore the potential synergy between these two methods and improve understanding of ergonomic factors in the work environment. Findings showed that integrating both methods allowed for more precise identification of critical body postures and customization of work procedures and equipment for individual workers. The results of the studied work process pointed out that work on the assembly line was associated with moderate fatigue according to the OWAS method, while the KIM method revealed significantly increased risks of physical strain in manual tasks. The results underline the importance of ergonomic analyses in creating better working conditions and improving worker productivity, which can positively impact employee’s health, satisfaction, and business performance. The results underline the importance of both analyses to objectively assess working conditions and improve worker’s productivity, which can positively impact employee’s health and satisfaction and company performance in the long term.